Discovery of novel pyrazole-containing benzamides as potent RORγ inverse agonists. Issue 15 (1st August 2015) - Wang, Tao; Banerjee, Daliya; Bohnert, Tonika; Chao, Jianhua; Enyedy, Istvan; Fontenot, Jason; Guertin, Kevin; Jones, Howard; Lin, Edward Y.; Marcotte, Douglas; Talreja, Tina; Van Vloten, Kurt
Graphical abstract